INTERFERENSI JARINGAN SENSOR NIKABEL DENGAN JARINGAN WIFI - Redaksi Tim Jurnal (Sekolah Tinggi Teknik PLN, 2016)
Interference is unavoidable in an environment where multiple wireless communication systems co-exist and work on a similar frequency band. Since a number of wireless technologies such as 6LowPAN, ZigBee, Bluetooth, and WiFi are all using the 2.4 GHz free-licence frequency band, the possibility of interference between them has to be addressed in any design and implementation of a WSN. This article initially identifies the causes of interference in WSNs and then introduces strategies for detecting and mitigating the interference, including maintaining physical and frequency separations between the victim systems and interferer and employing effective routing protocols.